2018
DOI: 10.1557/adv.2018.506
|View full text |Cite
|
Sign up to set email alerts
|

Material Reliability of Low-Temperature Boron Deposition for PureB Silicon Photodiode Fabrication

Abstract: The chemical-vapor deposition conditions for the growth of pure boron (PureB) layers on silicon at temperatures as low as 400°C were investigated with the purpose of optimizing photodiodes fabricated with PureB anodes for minimal B-layer thickness, low dark current and chemical robustness. The B-deposition is performed in a commercially-available Si epitaxial reactor from a diborane precursor. In-situ methods commonly used to improve the cleanliness of the Si surface before deposition are tested for a depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…However, for a similar 400°C deposition, we found considerable etching of the Si in the implanted p ? -regions, but none at all in the nonimplanted regions [29]. Such a difference was also observed on samples with 700°C B-deposition if the Si had been exposed to non-optimal surface treatments before deposition.…”
Section: Surface Analysismentioning
confidence: 61%
See 2 more Smart Citations
“…However, for a similar 400°C deposition, we found considerable etching of the Si in the implanted p ? -regions, but none at all in the nonimplanted regions [29]. Such a difference was also observed on samples with 700°C B-deposition if the Si had been exposed to non-optimal surface treatments before deposition.…”
Section: Surface Analysismentioning
confidence: 61%
“…Moreover, previous experiments using the same type of PureB diode test structures have shown that depositing on the implanted p ? -regions sometimes led to a weakening of B bonds [29]. This was seen in tests where the devices were exposed to the Si wet-etchant tetra-methyl ammonium hydroxide (TMAH).…”
Section: Surface Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…For B deposited below 250℃, the growth of the layer appears to stagnate at around 1 nm to 1.5 nm, as determined by in-situ ellipsometry. As opposed to higher temperature deposition [130], possibly the conditions at 250℃ resulted in a preference for the B to adsorb on Si sites rather than Bsites, leading to an almost self-limiting deposition [21]. SIMS analysis of these samples was carried out and the resulting B concentration is shown in Fig.…”
Section: Picosun B-layersmentioning
confidence: 99%
“…In contrast, for the PureB capping of detectors for SEM systems there has been no indication that the B surface is prone to oxidation, something which would negatively impact the signal gain of the photodiodes. Nevertheless, experiments have shown that contamination of the CVD system will readily lead to incorporation of oxygen in the B-layer [38], a danger that increases as the deposition temperature, and thus the deposition rate, is reduced. For synthesis of borophene, such contamination has been reported to be devastating.…”
Section: Boron As a Bulk Materialsmentioning
confidence: 99%